Agricultural application of domestic sludges on selected crops - Prayoon Chanya; Eckhardt, Ing. Heinz; Hansen, Gunner K.; Preeda Pakpian; Royal Thai Government (Bangkok : Asian Institute of Technology, 1998)
A pot study was conducted by using the neutral soil collected from garden area in Taling Chan district, Bangkok. Chinese kale and cabbage were selected to grown on BMA sludges-amended soil with optimum application rates, 100 and 150 kgN/ha. They have short period of growing time and therefore the opportunities of pathogen survival in plant surfaces should be considered. On the other hand, yields and heavy metal accumulations in crop tissues at the harvesting time were also evaluated. The results of pot experiments showed that pathogen survival on crop surfaces in regards of fecal coliforms were less than 2 MPN/gram wet weight and parasites were negative. This expresses that applications of BMA sludges to selected crops are safe in regards of pathogen contaminations at harvesting time. Considering the yields of Chinese kale and cabbage it was found that yields of kale grown on nightsoil sludge and sewage sludge application rate 150 kgN/ha were significantly higher than the control soil. The yields of kale and cabbage grown on the other treatments of BMA sludges did not significantly differ from the control soil. This was because the sludges needed time to mineralize and the fact that in the used soil some fertilizer residuals from the previous fertilizing activities have been pi·esent. Moreover, copper deficiency was found in experimental plants grown on the control soil. This indicates that copper deficiency in soil also played an important role to crop yields. According to the optimum yields obtained from the BMA sludges application rate 150 kgN/ha, heavy metals taken up by crops were evaluated. It was found that cadmium, copper, lead, nickel, manganese and zinc concentrations in kale and cabbage tissues were lower than or presenting in the normal concentrations of plant tissues. Only chromium concentration that was found slightly higher than the normal concentration, however; this gave no effect to crop yields. Interestingly, kale grown on selected soil showed the copper deficiency with low obtained yield. In contrast, kale grown on BMA sludges application rate 150 kgN/ha was observed the significant concentration of copper together with significant yield compared to the control soil. Therefore, BMA sludge application is regarded as beneficial due to improving the copper deficiency in the representative soil. Considering the accumulations of other metals in plant tissues, Huay Kwang sewage sludge and Nong Khaem nightsoil sludge application rate 150 kgN/ha, are safe and practicable. The results of pot study exhibit that Nong Khaem nightsoil sludge and Huay Kwang sewage sludge application rate 150 kgN/ha could promote the optimum yields with relatively safe and practicable in regards of pathogen contamination and heavy metal accumulations in crop tissues.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1998
Keywords: Sewage sludge as fertilizer